Organic micropollutants on river sediments from Rio de Janeiro State, Southeast Brazil Micro-poluentes orgânicos em sedimentos fluviais no Estado do Rio de Janeiro, Sudeste do Brasil - João Paulo Machado Torres; Olaf Malm; Elisa Diniz Reis Vieira; Jan Japenga; Gerwin Ferdinand Koopmans (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The paper is a contribution for the knowledge upon concentrations and fate of different kinds of organic micropollutants in Tropical River system from a very industrialized region in Brazil. The presented data was obtained during three years of an International Research Project between Brazilian and Dutch institutions. The sediments were sampled at the Paraiba do Sul-Guandu river watershed, the most important watercourse of Rio de Janeiro state, where up 90 % of the population depends on its water for domestic uses. After extraction with non-polar solvents in a hot sohxlet device and clean up using chromatographic columns, three classes of organic micropollutants were analyzed: organochlorine insecticides (OCs), polychlorinated biphenyls (PCBs) and polynuclear aromatic hydrocarbons (PAHs). The organochlorines, including the PCBs were scarcely present in the collected samples probably reflecting the restrictions of use of this class of compounds in the Brazilian market. However, the PAHs levels were high at the vicinity of a huge steelworks located in the city of Volta Redonda. This contamination is probably due to the massive use of coal in the above-cited metallurgical plant. Este artigo pretende contribuir para o conhecimento sobre a concentração e destino de diferentes tipos de micro-poluentes num sistema fluvial tropical de uma região brasileira altamente industrializada. Os dados apresentados foram obtidos ao longo de três anos, como parte de um projeto de pesquisa internacional envolvendo instituições brasileiras e holandesas. As amostras de sedimentos foram obtidas da bacia hidrográfica Paraíba do Sul/Guandu, a mais importante hidrovia no Estado do Rio de Janeiro, onde 90% da população depende dessa água para uso doméstico. Após extração com solventes não-polares num dispositivo sohxlet quente, e limpeza utilizando colunas cromatográficas, foram analisadas três classes de micro-poluentes orgânicos: inseticidas organoclorados (OCs), bifenis policlorados (PCBs) e outros hidrocarbonetos polinucleares (PAHs). Os organoclorados, inclusive os PCBs, estavam presentes em quantidades muito reduzidas nas amostras, provavelmente refletindo as restrições contra o uso dessa classe de compostos no mercado brasileiro. Entretanto, os PAHs mostravam níveis elevados ao redor de uma grande indústria siderúrgica na cidade de Volta Redonda. Tal contaminação deve-se, provavelmente, ao uso maciço de carvão nesta fábrica.